Capital Structure, Profitability, Hedging Policy, Firm Size, and Firm Value: Mediation and Moderation Analysis - Erik Syawal Alghifari; Ikin Solikin; Nugraha; Ika Waspada; Lilis Puspitawati (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to determine the impact of the capital structure on firm value through profitability moderated by hedging policies and firm size. Verification analysis is used in this study, with data analysis techniques through conditional process analysis. For the 2016-2020 period, the research population consists of a variety of industrial sector manufacturing companies listed on the Indonesia Stock Exchange. The results show that: capital structure has an impact on profitability; capital structure and profitability have an impact on firm value; profitability does not mediate the effect of capital structure on firm value, which is moderated by hedging policies and firm size; hedging policies and firm size moderate the direct effect of capital structure on firm value; and hedging policies and firm size do not moderate the indirect effect of profitability on firm value.